PHK Tidak Sesuai Prosedur Berdasarkan UU No. 13 Thn 2003 Tentang Ketenagakerjaan Jo UU No. 6 Thn 2023 Tentang Cipta Kerja Perspektif Maqashid Syariah (Studi Kasus PTSN No. 32/Pdt.G/2019/Pn Bau) - Husniyah Aufa; Fauziah Lubis (CV Rewang Rencang, 2025)
This study aims to analyze Termination of Employment (PHK) that does not follow proper procedures based on Law No. 13 of 2003 concerning Manpower, as amended by Law No. 6 of 2023 on Job Creation, from the perspective of maqashid syariah, using case number 32/Pdt.G/2019/PN Bau as a case study. The main issue in procedurally improper termination lies in the imbalance of bargaining power between workers and employers, as well as weak supervision over the implementation of regulations. This leads to procedural violations in employment termination, which often result in injustice, violations of workers’ rights, and legal uncertainty, ultimately affecting workers’ economic welfare. Employment termination is a frequent source of conflict between workers and employers, particularly when it is not carried out in accordance with the procedures stipulated in the legislation. This study uses a normative juridical approach by examining relevant legal regulations and linking them with the principles of maqashid syariah, particularly in terms of the protection of wealth (hifz al-mal) and the protection of life (hifz an-nafs). The findings indicate that the procedural violation of employment termination in this case contradicts the principle of justice as outlined in labor laws and the values of maqashid syariah. Although the Job Creation Law provides flexibility in employment relationships, its implementation often overlooks the protection of workers’ rights, resulting in economic losses for workers